2017
DOI: 10.2152/jmi.64.146
|View full text |Cite
|
Sign up to set email alerts
|

Influential factors on serum albumin concentration in hospitalized chronic kidney disease patients

Abstract: : Background : Serum albumin concentration (SAC) is a prognostic factor that is affected by many factors such as postural change, liver function and food intake. Chronic kidney disease (CKD) patients excrete proteinuria, have low-protein diet, and receive glucocorticoid therapy. No one has evaluated the most influential factors on SAC in CKD patients. Methods : A retrospective study. Hospitalized CKD patients with less than 1 g/ gCreatinine proteinuria receiving glucocorticoid therapy (n=28), with 1 or more g/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…There is a large overlap among outpatients with optimal DW and inpatients including !50% patients without practical DW (Figure 1, Table 3, 4). In addition, basically, inpatients have different nutritional status and hemodynamics with low serum albumin and hemoglobin concentration because of the change of diet and activity compared with outpatients (17). In this study, inpatients had lower serum albumin and hemoglobin concentration than outpatients ( Table 2).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…There is a large overlap among outpatients with optimal DW and inpatients including !50% patients without practical DW (Figure 1, Table 3, 4). In addition, basically, inpatients have different nutritional status and hemodynamics with low serum albumin and hemoglobin concentration because of the change of diet and activity compared with outpatients (17). In this study, inpatients had lower serum albumin and hemoglobin concentration than outpatients ( Table 2).…”
Section: Discussionmentioning
confidence: 61%
“…The markers of DW such as IVCdexp, CTR (1), left ventricular end-diastolic diameter (LVDd) (16), left atrial diameter (LAD) (17) were analyzed to investigate the best marker of DW in outpatients. First, IVCdexp, LVDd and LAD were related to body surface area, so that the markers were influenced by body size.…”
Section: Diameter Of Inferior Vena Cava In Outpatients and Inpatientsmentioning
confidence: 99%
“…For AHF patients with malignancy, liver cirrhosis, nephrotic syndrome, chronic kidney disease and sepsis, these comorbidities can affect the synthesis and concentration of albumin. [21][22][23][24] In subgroup analysis, it can be found that only sepsis had an impact on the relationship between serum albumin and LOS. Sepsis is systemic infectious disease that often leads to dysfunction of various organs of the body.…”
Section: Discussionmentioning
confidence: 99%